(untitled) (Bioscience Journal, 2023)
Maize silage has been used as a forage reserve strategy for critical periods or continuous use in animal feed. However, new genotypes and their potential must be identified. Thus, this study aimed to evaluate the potential of maize genotypes for silage and grain in one off-season in the midwest region of Brazil, under limited water and frost, and select them for this dual purpose (silage and grain) using the GT Biplot tool. The experiment was performed at Embrapa Western Agriculture in the autumn-winter season of 2021 in Dourados, Mato Grosso do Sul, Brazil. The experimental design consisted of randomized blocks of six maize genotypes (BRS1010, KWS9606, 1P2224, 1Q2383, BRS3046, and CAPO) with five replications under no-tillage. Silage points were evaluated at harvest when the grain milk line was at ¾ and maize grains at the maturation stage (dry plant). The 1P2224 and 1Q2383 maize genotypes present silage (high green and dry biomass) and grain yield potential. The GT Biplot tool identified the 1P2224 genotype as superior and suitable for cultivation or as a parent in a breeding program in the midwest region of Brazil for silage and grain yield evaluations of one off-season under limited water and frost.